온라인 쇼핑 상황에서 고객충성도의 결정요인: 인터넷 쇼핑과 모바일 쇼핑의 비교 분석 - 고준; 최수정; 안백성; Koh, Joon; Choi, Sujeong; An, Baicheng (한국콘텐츠학회 논문지, 15(11), 2015)
This study focuses on customer loyalty that explains how firms can maintain long-term relationship with customers, in the internet shopping and mobile shopping contexts. Specifically, this study examines the key determinants of customer loyalty from two perspectives: service quality and shopping value. Concerning service quality, previous studies have long argued that it is a starting point of building customer loyalty. Shopping value is a key variable in capturing consumers' shopping motives. In this study, we consider two types of shopping value: usefulness as utilitarian value and enjoyment as hedonic value. Moreover, this study examines whether the effects of service quality and shopping value on customer loyalty differ depending on internet and mobile shopping groups. To test the proposed hypotheses, we conducted multiple linear regression analysis and chow test with a total of 199 data collected on users who have experience in internet shopping and mobile shopping. The key findings are as follows: First, in the internet shopping group, customer loyalty depends on service quality (responsiveness and empathy) and usefulness, whereas in the mobile shopping, it only depends on enjoyment. Second, the impacts of service quality and shopping value on customer loyalty are different depending on internet shopping and mobile shopping. The results imply that e-tailors should develop differential methods suitable for internet shopping or mobile shopping to enhance customer loyalty. 본 연구는 인터넷 쇼핑과 모바일 쇼핑에서 현재의 소비자들을 장기적으로 유지하는 문제 즉, 어떻게 이들로부터 고객충성도를 이끌어 낼 것인가를 연구하고자 한다. 구체적으로, 본 연구는 각각의 쇼핑 환경에서 고객충성도에 가장 영향력 있는 변수가 무엇인지를 비교, 규명하고자 한다. 수많은 선행연구들에서 고객충성도의 출발점은 우수한 서비스품질임을 강조하였다. 이에, 본 연구는 서비스품질을 고객충성도의 핵심 선행변수로 고려한다. 또 다른 선행변수로써 실용적 가치인 유용성과 쾌락적 가치인 즐거움을 제시한다. 마지막으로, 본 연구는 인터넷 쇼핑과 모바일 쇼핑의 각 집단에서 서비스품질 및 쇼핑가치가 고객충성도에 미치는 효과에 차이가 존재하는지를 분석한다. 실증분석 결과는 첫째, 인터넷 쇼핑 집단에서는 쾌락적 가치인 즐거움을 제외한 나머지 선행변수들 즉, 서비스품질 차원인 대응성과 공감성 그리고 실용적 가치인 유용성이 모두 고객충성도를 증가시키는 것으로 나타난 반면에, 모바일 쇼핑 집단에서는 즐거움만이 고객충성도에 유의하였다. 둘째, 서비스품질 및 쇼핑가치가 고객충성도에 미치는 효과는 인터넷 쇼핑 및 모바일 쇼핑에 따라 명백한 차이가 존재하는 것으로 나타났다. 이 결과는 각각의 쇼핑에 효과적인 고객충성도 관리방법이나 전략이 다를 수 있음을 시사한다.